Effects of vitamin D deficiency on bone and root re-sorption post-orthodontic retention in rats - Asmaa M Khamees; Dheaa H Al Groosh; Natheer H Al-Rawi (College of Dentistry/ University of Baghdad, 2023)
Background: Orthodontic therapy often causes external root resorption. Serum vitamin D (VD) level is important for tooth mineralization and bone remodeling. This study aimed to test the impact of vitamin D (VD) supplements on bone and root remodelling in a vitamin D (VD) deficient rat model following orthodontic retention. Methods and Material: 30 male Wistar rats were divided into three groups: a control group of 10 rats and two experimental groups of 10 rats each with vitamin D deficiency (VDD) induced by a VD-free diet for 21 days. And a third group with VD supplementAll groups received orthodontic active treatment using a modified orthodontic appliance that applied 50 gm of force for 14 days to move the maxillary right first molar mesially, followed by 7 days of retention and relapse. The VDD group received no intervention, while the VDS group received 40,000 IU/kg of systemic VD3 by intramuscular injection on the first and fifteenth day of orthodontic treatment. Histomorphometric analysis was performed to assess bone and cementum resorption and deposition. Results: The VDD group exhibited a significant increase in bone and root resorption and a decrease in bone deposition and ce-mentum deposition ratio. In addition, bone deposition and the ratio of cementum deposition were substantially greater in the VDS group compared to the control group. Conclusion: VDD may increase bone and root cementum resorption and decrease deposition after orthodontic retention, which may play a significant role in relapse after retention. Prior to beginning orthodontic treatment, routine VD screening may be beneficial.